SOCIAL AND LEGAL NORMATIVISM. TRADITION AND PRESENT - Marius ANDREESCU; Andra PURAN (Challenges of the Knowledge Society)
The most striking expression of the social fact is the social norm. Man's social existence cannot be conceived without norms, mainly moral, religious and legal, that regulate and even determine the behavior of the human person in the social environment. The existence of any individual as a social being presupposes a series of obligations exercised throughout his life cycle, materialized in a series of norms, some of which complement each other, others appear contradictory to others, being specific to different interest groups. This system of rules is a condition for the existence of society's life, a mechanism that requires good management of human relations and removes the imminent danger of chaos. Social norms are imposed, promoted and perpetuated by several methods that we will analyze in our study Regardless of the field they regulate, social norms contain rules addressed to individuals, describing and detailing the ways in which values must be translated into legitimate behaviors and accepted by society. As social relations are extremely varied, a diversity of social norms that regulate these relations is also outlined. Thus, the system of social norms consists of the following groups: ethical norms, ordinary norms (customs), corporate norms, religious norms and legal norms. There are also technical norms that are not part of social determinism because they do not regulate social relations. Regarding the complex relationship between the normative legal system and, on the other hand, society, it can be seen that currently the legal system tends to have its own functional autonomy, apart from the objective or subjective determinations that society transmits. The autonomy of the judiciary tries to transform itself from a secondary, phenomenological and ideational structure, into one with its own reality, with the power to impose its order on the social and natural order. In this study we also analyze aspects of the work of normative codification.